Cation Tuning of Supramolecular Gel Properties A New Paradigm for Sustained Drug Delivery - Ramin, Michael A (Advanced materials (Deerfield Beach, Fla.), 2017)
© 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.